On debt neutrality in the savers-spenders theory of fiscal policy - Alberto Petrucci (Fondazione Eni Enrico Mattei (FEEM), 2000)
According to the recent literature, heterogeneity across households does not invalidate debt neutrality in the long-run. The doctrinal view is at odds with the layman's view, on the basis of which government debt, by altering the intragenerational distribution of resources, may exert permanent effects on consumption, labour and therefore capital. This paper develops an intertemporal optimizing ''savers-spenders'' model of capital formation with endogenous labour choices to investigate if the intuitive view has some theoretical support. We discover that Ricardian equivalence is not an ineluctable law of a heterogeneous world. Two dimensions of heterogeneity matter for supporting debt nonneutrality: the savers-spenders distinction, on the one side, and the diversity in tastes, on the other. The dynamic effects of debt are large for some individual variables and factor prices, but may be reduced for aggregate demand and output. The paper shows that in a heterogeneous world also the hypothesis of recursive-time preferences undermines long-run debt neutrality.
Keywords: 330; Öffentliche Schulden; Ricardianische Äquivalenz; Generationengerechtigkeit; Theorie